Relationship Between Stress And Ear-Nose-Throat Disorder Exam Values In Medical Education Students Of The Faculty Of Medicine, Sam Ratulangi University - Gebriela Naomi Waani; Linda Maya Tompodung; Heriyannis Homenta (Jurnal Impresi Indonesia, 2025)
Stres academic is one of significant challenges? for student medicine, especially Because burden dense and demanding curriculum? high academic. Stress? This can influence performance academic in a way direct and also No directly. Research This focus on relationships between level stress and results exam module Disturbance Ear Nose Throat (ENT-KL) in students medical class of 2022 at Sam Ratulangi University . Research This aiming For analyze connection between level stress experienced? students and results mark exam module ENT-KL disorders, as well as give outlook related interventions that can done For support welfare students. Research use design observational analytic with cross-sectional approach. The sample consists of of the 204 students who met the requirements criteria inclusion. Stress level measured use Perceived Stress Scale (PSS-10) instrument, while mark exam module obtained from notes academic official. Analysis done using the Spearman-rho correlation test to determine connection between level stress and results mark exam. Most of student be at the level stress moderate (71.1%) and successful to obtain A grade (92.6%) on the exam module. The Spearman-rho test shows No existence connection significant between level stress and value test (p = 0.756; r = 0.022). Findings This show that level stress No in a way direct influence achievement academic student in module this. Research results This indicates that although level stress currently often experienced by students, this is the No always become barrier for achievement academic. Support institutional, such as training management stress and counseling, can help student with level stress tall For reach balance between pressure academic and performance.